Modul Inovatif Pembelajaran Batakologi dengan Pendekatan Konstruktivistik - Nurliani Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
The purpose of this study is to develop a learning model Batakologi and lead innovative module products with constructivist approaches, for class VIII Junior High School. Data collected in the research and development using qualitative descriptive analysis of the implementation and results of the design development of the model. The development consists of three steps, namely (1) the preliminary draft that consisted of literature studies, requirements analysis, and documentation, (2) the development stage consists of the development of learning Batakologi, syllabi, evaluations, expert validation and revision (3) the implementation phase consisting of limited testing and revision, eld trials and revisions, and the final model. The product of this research is the book Batakologi Innovative learning modules and teacher guidebooks that the application can be used by students and teachers, the source comes from the tradition of the Batak culture.